Missense mutations in the human SDHB gene increase protein degradation without altering intrinsic enzymatic function - Yang, Chunzhang (Federation of American Societies for Experimental Biology, 2012)
Mutations of succinate dehydrogenase subunit B (SDHB) play a crucial role in the pathogenesis of the most aggressive and metastatic pheochromocytomas (PHEOs) and paragangliomas (PGLs). Although a variety of missense mutations in the coding sequence of the SDHB gene have been found in PHEOs and PGLs, it has been unclear whether these mutations impair mRNA expression, protein stability, subcellular localization, or intrinsic protein function. RT-PCR and Western blot analysis of SDHB mRNA and protein expression from SDHB-related PHEOs and PGLs demonstrated intact mRNA expression but significantly reduced protein expression compared to non-SDHB PHEOs and PGLs. A pulse-chase assay of common SDHB missense mutations in transfected HeLa cell lines demonstrated that the loss of SDHB function was due to a reduction in mutant protein half-life, whereas colocalization of SDHB with mitochondria and immunoprecipitation with SDHA demonstrated intact subcellular localization and complex formation. The half-life of the SDHB protein increased after treatment with histone deacetylase inhibitors (HDACis), implicating the protein quality control machinery in the degradation of mutant SDHB protein. These findings provide the first direct mechanism of functional loss resulting from SDHB mutations and suggest that reducing protein degradation with HDACis may serve as a novel therapeutic paradigm for preventing the development of SDHB-related tumors.—Yang, C., Matro, J. C., Huntoon, K. M., Ye, D. Y., Huynh, T. T., Fliedner, S. M. J., Breza, J., Zhuang, Z., Pacak, K. Missense mutations in the human SDHB gene increase protein degradation without altering intrinsic enzymatic function.